Assessment of intracardiac flow dynamics for the evaluation of patients with aortic stenosis. (14th October 2021) - Strangio, A; Sabatino, J; Leo, I; Maglione, M; Troilo, F; Loliva, G; Canino, G; Spaccarotella, C A; De Rosa, S; Indolfi, C
Abstract: Background: Assessment of intracardiac flows and turbulence has acquired rising significance in the past few years, due to the development and introduction of technologies for non-invasive cardiovascular imaging. Recent studies have shown that alterations in intracardiac fluid dynamics can be helpful to identify abnormalities in cardiac function. Purpose: This study investigates the additional information provided by the quantitative assessment of intracardiac flow dynamics for the evaluation of patients with aortic stenosis (AS), by using an advanced echocardiography vortex-based approach. Methods: Sixty-one patients with severe AS (33 females) and 38 healthy sex- and BSA-matched controls (CTRL) (15 females) were prospectively included and underwent echocardiographic assessment of intracardiac flow dynamics. Echocardiographic measurements were performed on apical three chamber views. The HyperDoppler software adapted to the echo-scanner without contrast injection was used to assess intracardiac vortex properties. The following parameters were obtained: vortex area (VA) (the ratio between the total vortex area and the left ventricular (LV) area); vortex length (VL) (the longitudinal length of the vortex relative to the total LV length; vortex depth (VD) (the distance of the vortex center from the LV base relative to the total LV long axis). Inter-rater variability was measured using intraclass correlation coefficients (ICCs) between two independent operators. Results: Patients with severe AS (mean gradient: 47, 5±13, 9 mmHg; aortic valve area: 0.7±0.2 cm 2 ; ejection fraction: 53±7%) had increased LV wall thickness (p<0.001) and mass index (p<0.001) compared with controls. Greater indexed left atrial volume (p<0.001), E/e' (p<0.001) and trans-tricuspid gradient (p<0.001) were also observed in the AS group. The assessment of VA, VL and VD was feasible in the whole population. Their calculation was reliable, as ICCs were very good for VA (0.878, p=0.033), VL (0.960, p=0.004) and VD (0, 905, p=0.021). Mean VA was significantly larger in patients with severe aortic stenosis compared with CTRL (p=0.033). VL and VD (p=0.026 and p>0.001, respectively) were significantly higher in AS patients compared with CTRL. Among those who underwent TAVR, we observed a significant difference in the delta values of VA and VL pre-postTAVR in patients with and without significant paravalvular leak (p<0.05). Conclusions: The newly defined VA, VL and VD, quantitative indices of vortical flow, were significantly increased in the LV cavity of patients with severe AS compared to normal subjects. These indices, whose measurement was feasible and reliable, might provide complementary information to standard echocardiography, useful for the further diagnostic and prognostic characterization of the heterogeneous population of patients with severe AS. Funding Acknowledgement: Type of funding sources: None.